Extracting Hydrophilic Components from Pomegranate Peel and Pulp - Samir Gharib Hafizov; Olga N. Musina; Gharib Kerim Hafizov (Техника и технология пищевых производств)
Pomegranate (Punica granatum L.) processing focuses on the extraction of polyphenols from peel. However, pomegranate peel is also rich in other biologically active water-soluble components, and their commercial extraction remains understudied. The research objective was to evaluate the degree of extraction of hydrophilic substances, such as simple sugars, organic acids, and polyphenols, from raw pomegranate peel and pulp under different experimental conditions in order to select the optimal extraction parameters. The study featured pomegranates of the Iridanaly variety (Geokchay, Azerbaijan). Raw peel and pulp were crushed to the state of a coarse gruel. Extraction occurred by maceration at a hydromodulus of 1:2 and a temperature of 40 or 60°C with pure water and aqueous ethanol solutions (10–14 % vol.). The process lasted 30, 60, or 90 min in one or two stages with separate extraction at each stage. The research involved standard physicochemical methods. In 31.0 ± 2.0 g/100 g of dry peel, the hydrophilic fraction accounted for 85.32%; in 35.7 ± 2.8 g/100 g of dry pulp, it was 59.36%. Only 54.6% solids were extracted from raw peel after 30 min of extraction with pure water at a hydromodulus of 1:2 and 60°C. Pomegranate peel contained hydrophilic colloids, which caused water absorption and reduced the yield. The optimal extraction included an aqueous solution of ethanol with an ethanol concentration of 10–14 % vol. and two thirty-minute stages. The coagulating effect of ethyl alcohol on water-soluble pectin made it possible to increase the degree of extraction of water-soluble substances to 83.93 and 91.4% of their initial content in raw peel and raw pulp, respectively. Such extraction yielded 4 kg of mixed extract from 1 kg of raw pulp. The extract was boiled under vacuum and yielded 260 g of concentrate with 60 wt.% solids, including 46.70 g/100 g simple sugars, 4.73 g/100 g organic acids, 3.70 g/100 g polyphenols, and 10.10 mg/100 g vitamin C. The extraction of raw pomegranate peel and pulp with aqueous ethanol (10–14 % vol.) provided the maximal degree of extraction of hydrophilic substances and facilitated the separation of the resulting extracts. However, strong alcohol solutions may increase the cost of distillation of alcohol from the extract. To eliminate this shortcoming, the extraction can be carried out with pure water and a pectolytic enzyme.